PEMEROLEHAN BAHASA PERTAMA ANAK USIA DINI MELALUI TAYANGAN ANIMASI NUSSA DAN RARA - Intan Pertiwi Sirait; Diah Kusyani; Sri Muliatik (Fakultas Teknik Universitas Negeri Makassar, 2026)
This study aims to analyze the first language acquisition (L1) of early childhood students at TK Mawar through the screening of the animated film Nussa and Rara. This research employs a descriptive qualitative method with data collection techniques in the form of observation and documentation of children aged 3–4 years. The study focuses on the early stage of language acquisition by utilizing audiovisual media. Linguistic stimulation presented repeatedly through the animated film Nussa and Rara triggers children's language skills. Children who receive this stimulation show development in linguistic aspects, including phonology, morphology, syntax, semantics, and pragmatics. They are able to imitate speech sounds clearly, use simple affixes appropriately, construct sentences according to the subject–predicate–object–adverb (SPOK) structure, understand new vocabulary, and adjust their speech according to social contexts. Based on the findings, it can be concluded that audiovisual media such as the animated film Nussa and Rara not only provide entertainment but also serve as an effective educational tool in supporting early childhood first language acquisition.